Chemical Modification of Unwanted Flora (Hanguana Malayana) as Activated Carbon to Remove Methylene Blue and Congo Red - Intachai, Sonchai; Juntarachat, Niramol; Sumanatrakul, Panita (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.26, 2021)
Wastewater is well-known hot issue of environmental pollutions that require a solution hurriedly.  Organic dye is a severe toxic contaminant in water.  In this work, Hanguana Malayana used as carbon source was chemically activated as activated carbon.  The biochar was carried out by the pyrolysis through the heat treatment at 200 °C under low O 2 atmosphere.  The resulting powder was activated by using ZnCl 2 under hydrothermal conditions at 120 °C for 24 h, and further heat-treated at 300 °C for 1 h.  The as-prepared product was verified by XRD, FT-IR, SEM, and BET.  There were large surface area and many functional groups on the surface of the as-prepared product.  All amounts of methylene blue (20 ppm, 50 mL) were removed by 50 mg of activated carbon, meanwhile very few amounts of Congo red (20 ppm, 50 mL) were eliminated.  This work showed the benefits on increasing an add-value of Hanguana Malayana by the chemical process together with eliminating unwanted flora and toxic dye chemicals in water. Keywords: methylene blue, Congo red, activated carbon, adsorption, Hanguana malayana